Does Health Protocol Contribute to the Indonesia’s Economic Growth in COVID 19 Pandemic? - Wiwin Priana; Dewi Khrisna Sawitri (Ilomata International Journal of Social Science, 2021)
The COVID-19 has effected many aspects of life within a year. Some countries have declared to lockdown their nations in order to protect their citizens. That also happens in Indonesia. Many efforts are conducted to restrict human interaction and it directly has impacted a lot for business and economy sector. In the beginning, the emerge of COVID-19 in Indonesia had directly decreased the economic growth. It also gives impact on the next growth during year 2020. Finally, It results in the average of economic growth in overall 2020. This research explores the data of economic growth from taken from BPS. The result shows the economic growth in percentage and it also shows how the economic growth declines. This research also tries to elaborate the existence of government policy in Public Health sector that try to stimulate to the operational of business. Health Protocol is implemented for business during this pandemic though its implementation cost more money.